2012
DOI: 10.1007/s13679-012-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Adrenal Axis, Obesity, and Chronic Stress Exposure: Foods and HPA Axis

Abstract: The prevalence of overweight and obesity has increased worldwide to epidemic proportions. Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and chronic stress exposure are hypothesized to contribute to obesity development. In this review, we discuss the potential role of the HPA axis for energy balance regulation, with particular attention to energy intake. We present evidence from human and animal studies that highlight the bidirectional relationship between HPA axis functioning and energy intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 99 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…A further possible explanation in view of the mechanism of stress-induced eating might be the alterations of the hypothalamic-pituitary-adrenocortical (HPA) axis in obesity, as the latter cortisol metabolism with regard to basal level and stress reactivity 19 . A disturbed feedback loop of the HPA axis may lead to resistance of adiposity signals in different body areas 21 . With regard to the selfish brain theory 37 , one possible mechanism might be altered signals from the HPA axis to the brain, resulting in failing regulatory processes of the energy balance and eating behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further possible explanation in view of the mechanism of stress-induced eating might be the alterations of the hypothalamic-pituitary-adrenocortical (HPA) axis in obesity, as the latter cortisol metabolism with regard to basal level and stress reactivity 19 . A disturbed feedback loop of the HPA axis may lead to resistance of adiposity signals in different body areas 21 . With regard to the selfish brain theory 37 , one possible mechanism might be altered signals from the HPA axis to the brain, resulting in failing regulatory processes of the energy balance and eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study by Epel et al 6 , we hypothesized that healthy weight HCR would tend to eat more in response to acute stress than the low reactors (hypothesis 1). Given the greater cortisol reactivity of people with obesity 19 and the effect of cortisol on food intake 21 , we hypothesized that obese HCR would show greater stress-induced food intake compared to low reactors (hypothesis 2). With regard to the link between basal cortisol level, cortisol reactivity, and eating behavior 6,22 , we hypothesized that healthy weight HCR would exhibit higher basal cortisol levels than the low reactors (hypothesis 3).…”
Section: Objectivesmentioning
confidence: 99%
“…Emerging research suggests that the hypothalamic‐pituitary‐adrenal (HPA) axis plays an important role in metabolism and fat distribution and that the excessive stimulation of the HPA axis in response to an increased amount of stress contributes to the development of obesity (Rutters et al, ). A rise in morning cortisol among healthy adults is regarded as a physiological indicator of the HPA axis' stress responsivity (Pruessner et al, ) and is expected to be positively associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that increased plasma cortisol level is directly related to weight (Bose, Olivan, & Laferrere, 2009;Rutters et al, 2012). This relationship is well seen in patients with hyper or hypoadrenalism where one of the symptoms include weight gain and weight loss respectively.…”
Section: Hypothalamic Pro-inflammatory Cytokines and Obesitymentioning
confidence: 83%